In vivo study of cone beam computed tomography texture analysis of mandibular condyle and its correlation with gender and age - Nussi, Amanda Drumstas; Lopes, Sérgio Lucio Pereira de Castro [UNESP]; Rosa, Catharina Simioni de; Gomes, João Pedro Perez; Ogawa, Celso Massahiro; Braz-Silva, Paulo Henrique; Costa, Andre Luiz Ferreira (Springer Nature, 2022)
Objective: Texture analysis is an image processing method that aims to assess the distribution of gray-level intensity and spatial organization of the pixels in the image. The purpose of this study was to investigate whether the texture analysis applied to cone beam computed tomography (CBCT) images could detect variation in the condyle trabecular bone of individuals from different age groups and genders. Methods: The sample consisted of imaging exams from 63 individuals divided into three groups according to age groups of 03–13, 14–24 and 25–34. For texture analysis, the MaZda® software was used to extract the following parameters: second angular momentum, contrast, correlation, sum of squares, inverse difference moment, sum entropy and entropy. Statistical analysis was performed using Mann–Whitney test for gender and Kruskal–Wallis test for age (P = 5%). Results: No statistically significant differences were found between age groups for any of the parameters. Males had lower values for the parameter correlation than those of females (P < 0.05). Conclusion: Texture analysis proved to be useful to discriminate mandibular condyle trabecular bone between genders.
Keywords: Bone; Cone beam computed tomography; Image processing; Radiomics; Temporomandibular joint